Distributed Computing 25th International Symposium, DISC 2011, Rome, Italy, September 20-22, 2011. Proceedings - Peleg, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 25th International Symposium on Distributed Computing, DISC 2011, held in Rome, Italy, in September 2011. The 31 revised full papers presented together with invited lectures and brief announcements were carefully reviewed and selected from 136 submissions. The papers are organized in topical sections on distributed graph algorithms; shared memory; brief announcements; fault-tolerance and security; paxos plus; wireless; network algorithms; aspects of locality; consensus; concurrency.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Artificial intelligence; Computer Science; Computer Communication Networks; Software Engineering; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Programming Techniques; Artificial Intelligence (incl. Robotics).